2016
DOI: 10.1155/2016/9027484
|View full text |Cite
|
Sign up to set email alerts
|

Mean Daily Dosage of Aspirin and the Risk of Incident Alzheimer’s Dementia in Patients with Type 2 Diabetes Mellitus: A Nationwide Retrospective Cohort Study in Taiwan

Abstract: Background. Type 2 diabetes mellitus patients are known to have higher risk of developing dementia while aspirin use has been shown to prevent incident dementia. This study was conducted to evaluate the potential benefits of aspirin use on dementia in patients with type 2 diabetes mellitus and identify the appropriate dosage of aspirin that provides the most benefit. Method. A Taiwan nationwide, population-based retrospective 8-year study was employed to analyze the association between the use of aspirin and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…These 16 cohort studies including 236,022 participants, published between 1995 and 2016 were identified for analysis on the associations between NSAID use and risk of AD (Breitner et al, 1995 , 2009 ; Stewart et al, 1997 ; in t' Veld et al, 2001 ; Zandi et al, 2002 ; Landi et al, 2003 ; Nilsson et al, 2003 ; Cornelius et al, 2004 ; Arvanitakis et al, 2008 ; Fischer et al, 2008 ; Szekely et al, 2008 ; Ancelin et al, 2012 ; Côté et al, 2012 ; Chang et al, 2016a , b ; Wichmann et al, 2016 ). Characteristics of the included studies are presented in the Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 16 cohort studies including 236,022 participants, published between 1995 and 2016 were identified for analysis on the associations between NSAID use and risk of AD (Breitner et al, 1995 , 2009 ; Stewart et al, 1997 ; in t' Veld et al, 2001 ; Zandi et al, 2002 ; Landi et al, 2003 ; Nilsson et al, 2003 ; Cornelius et al, 2004 ; Arvanitakis et al, 2008 ; Fischer et al, 2008 ; Szekely et al, 2008 ; Ancelin et al, 2012 ; Côté et al, 2012 ; Chang et al, 2016a , b ; Wichmann et al, 2016 ). Characteristics of the included studies are presented in the Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Several epidemiologic studies showed that patients treated with NSAIDs had a decreased risk for developing AD (Breitner et al, 2009 ; Côté et al, 2012 ; Chang et al, 2016a , b ). However, this evidence was only based on observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our research has shown that aspirin, one of world's oldest pharmaceutical agents, exhibits a diverse range of effects in the amelioration AD pathogenesis and subsequent protection of hippocampal neurons (Figure ). Although some studies indicate beneficial role of aspirin in AD (Chang, Horng, Hsu, & Chen, ; Etminan, Gill, & Samii, ; Nilsson et al, ; Wang et al, ), couple of studies contradict such favorable function of aspirin. For instance, Kelley et al () do not find any significant relationship between the daily aspirin use and cognitive change over 2 to 6 years of follow‐up after controlling for the impact of age.…”
Section: Resultsmentioning
confidence: 99%
“…First, although no distinct mechanisms of statins exist to explain their effects on dementia protection, many studies have discussed their cholesterol-lowering effects and pleiotropic effects, including the beta-amyloid deposition, anti-thrombotic effects, or anti-inflammatory effects of statins related to dementia protection [16,[33][34][35][36]. In addition, since IHD is a well-known risk factor for dementia, anti-hyperlipidemia, anti-platelet, and anti-hypertensive therapy have been suggested to reduce the risk of dementia [37,38]. These findings may help to clarify the beneficial effects of statins on dementia in statin users and non-users with a PS-matched baseline.…”
Section: Discussionmentioning
confidence: 99%